1999
DOI: 10.3186/jjphytopath.65.526
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Pathogenic Races of Rice Blast Fungus in Vietnam.

Abstract: One hundred and twenty-nine monoconidial isolates of Pyricularia grisea from rice were collected in Vietnam, mainly in the Mekong River Delta (MRD), in 1995-1996 to characterize their virulence. These isolates were classified into 12 pathogenic groups (races) based on their virulence to 12 Japanese differential rice varieties (modified Kiyosawa's differentials). Race 002.4 was predominant and was found in 10 provinces of MRD, followed by races 106.4, 006.4, 102.4 and 002.0. Differential varieties Aichi Asahi (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…These numbers of pathotypes suggest the existence of wide genetic variability of blast races in the Philippines. This result agreed with the cases of Vietnam 20,21 , Thailand 19 and China 3 . The five DVs, Kanto 51 for Pik, K3 for Pik-h, Tsuyuake for Pik-m, K60 for Pik-p, and C101LAC for Pi1, showed similar reaction patterns.…”
Section: Classification Of Blast Isolates Based On the Reaction Pattesupporting
confidence: 81%
See 1 more Smart Citation
“…These numbers of pathotypes suggest the existence of wide genetic variability of blast races in the Philippines. This result agreed with the cases of Vietnam 20,21 , Thailand 19 and China 3 . The five DVs, Kanto 51 for Pik, K3 for Pik-h, Tsuyuake for Pik-m, K60 for Pik-p, and C101LAC for Pi1, showed similar reaction patterns.…”
Section: Classification Of Blast Isolates Based On the Reaction Pattesupporting
confidence: 81%
“…Inukai et al 10 reported that three Japanese DVs, Shin 2, Fukunishiki and Kusabue, showed the unique reactions of moderate resistance to almost all blast isolates from the Philippines, and an additional resistance gene was assumed to harbor these genetic backgrounds. Noda et al 21 had identified 12 kinds of blast races among 129 isolates collected all over the Mekong River Delta area in Vietnam using the Japanese DVs for 12 resistance genes by Yamada et al 27 and Kiyosawa 11,13 , and also reported that several DVs among them were not suitable for differentiations of blast isolates in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…Noda et al 14 13 , and the Philippines 17,22 , but few blast isolates were classified into each race, and no dominant blast races were found. It is difficult to compare our Cambodian data with those from these previous studies, because the numbers The blast isolates were classified into 3 cluster groups, I, IIa, and IIb, based on the reaction patterns of 25 DVs and LTH; 14 pathotypes, namely U63, i0, i7, k000, k100, z00, z04, z06, ta000, ta002, ta003, ta403, ta421 and ta431, were dominant.…”
Section: Discussionmentioning
confidence: 99%
“…These differential cultivars have been used in many studies, including determination of the presence of known resistance genes in rice cultivars, clarification of allelic relationships on resistance genes with known genes; and identification of novel resistance genes (Inukai et al 1994, Pan et al 1996. However, these differential Japanese cultivars are not well adapted to tropical blast isolates and have additional genes that can mask the target gene's reaction (Noda et al 1999. Moreover, an additional resistance gene, Pish, is carried in the genetic background of several of these differential cultivars (Imbe and Matsumoto 1985).…”
Section: Introductionmentioning
confidence: 99%